Chronic subdural haematoma preceded by persistent traumatic subdural fluid collection. Issue 12 (December 1987) - Ohno, K; Suzuki, R; Masaoka, H; Matsushima, Y; Inaba, Y; Monma, S
Abstract : The role of traumatic subdural fluid collections in the development of chronic subdural haematomas was studied in 43 of 715 patients who underwent a CT scan because of a recent head injury. Twenty of the 43 patients subsequently developed a chronic subdural haematoma, and this occurred especially in the aged. Nearly 50% of patients with asymptomatic or minimally symptomatic subdural fluid collection may develop a chronic subdural haematoma.